THE EFFECT OF SHRIMP PROTEIN HYDROLYSATE FORTIFICATION (Acetes erythareus) ON THE QUALITY OF RICE FLOUR INSTANT PORRIDGE - Yova, Surya Dirga; Suparmi, Suparmi; Dewita, Dewita (Aurelia Journal, 2025)
The demand for nutritious and practical instant food products continues to increase; however, many rice flour–based instant porridges still have low protein content, indicating the need for fortification innovations to enhance their nutritional value. Rebon shrimp (Acetes erythareus) is an abundant protein source with potential use as a fortification ingredient, yet its application in the form of protein hydrolysate and the optimal concentration required to improve product quality have not been extensively studied. This study aimed to determine the effect of rebon shrimp protein hydrolysate fortification on the quality of rice flour–based instant porridge and to identify the best concentration that produces an optimally formulated product. The research employed a Completely Randomized Design (CRD) with four treatments: B0 (0%), B5 (5%), B10 (10%), and B15 (15%) addition of protein hydrolysate based on the weight of rice flour. The parameters tested included organoleptic attributes (appearance, aroma, taste, and texture) and chemical analysis (moisture, ash, protein, fat, and carbohydrate contents). The results demonstrated that fortification with rebon shrimp protein hydrolysate significantly affected all quality parameters tested. The B10 treatment produced the best quality, with scores for appearance (8.28), aroma (7.48), texture (8.39), taste (7.08), and nutritional composition including moisture (4.82%), ash (1.99%), protein (9.20%), fat (3.35%), and carbohydrates (89.15%), all of which meet the quality standards for instant porridge based on SNI 01-7111.4-2005. It can be concluded that fortification with 10% rebon shrimp protein hydrolysate is the optimal concentration for improving the quality and nutritional value of rice flour–based instant porridge.